Reconstruction of Holocene coupling between the South American Monsoon System and local moisture variability from speleothem δ18O and 87Sr/86Sr records. (15th April 2019) - Ward, Brittany Marie; Wong, Corinne I.; Novello, Valdir F.; McGee, David; Santos, Roberto V.; Silva, Lucas C.R.; Cruz, Francisco W.; Wang, Xianfeng; Edwards, R. Lawrence; Cheng, Hai
Abstract: Investigating controls on past variability of South American hydroclimate is critical to assessing its response to future warming scenarios. δ 18 O records from South America offer insight into past variability of the South American Monsoon System (SAMS). The controls, however, on precipitation δ 18 O values can be decoupled from precipitation amount at a given site and, thereby, limit local moisture condition reconstructions. Here we use a principal components analysis to assess the coherence of speleothem and lake core Holocene δ 18 O records in tropical and subtropical South America to evaluate the extent to which δ 18 O variability reflects changes in SAMS intensity at different sites across the region. The main mode of variability across Holocene δ 18 O records (PC1) closely tracks austral summertime insolation, consistent with existing work. Sites towards the periphery of the continent are heavily weighted on PC1, whereas interior sites as not. Further δ 18 O variability at interior sites bear little similarity to each other and implicate controls, beyond regional monsoon intensity, on these δ 18 O records. Further, we develop speleothem 87 Sr/ 86 Sr records spanning the Holocene from Tamboril Cave (Brazilian Highlands), Paraíso Cave (eastern Amazon Basin), Jaraguá Cave (Mato Grosso do Sul Plateau), and Botuverá Cave (Atlantic coastal plain) to investigate coupling between reconstructed monsoon variability (reflected by PC1) and local moisture conditions (interpreted from 87 Sr/ 86 Sr records). We interpret speleothem 87 Sr/ 86 Sr variability as a proxy of local moisture conditions, reflecting the degree of water-rock interaction with the cave host rock as driven by variations in water residence time. Speleothem 87 Sr/ 86 Sr records from all the sites, except Botuverá cave, do not co-vary with PC1, suggesting that local moisture conditions do not necessarily follow variations in regional monsoon intensity at these interior sites. These speleothem 87 Sr/ 86 Sr records generally suggest dry mid-Holocene conditions relative to the early- and late-Holocene, consistent with interpretations of other paleo-moisture records in the region, but timing of wet-dry transitions varies between sites. These results highlight that controls, in addition to SAMS variability, might influence δ 18 O variability. Further, our results suggest spatially variable local moisture conditions at interior sites that do not uniformly respond to regional monsoon intensity, and stress the need for δ 18 O-independent reconstructions of moisture conditions. Highlights: The main mode of speleothem δ 18 O variability follows austral summertime insolation. Speleothem 87 Sr/ 86 Sr values are a feasible proxy of local moisture conditions at our study sites. Local moisture conditions are largely decoupled from overall monsoon intensity. Speleothem 87 Sr/ 86 Sr values suggest a widespread mid-Holocene drying across study sites.